List of reviewers EQ21 and EQ22 / 2015 - .., . (Ecological Questions, 2016)
Isabel Alonso, Natural England, Temple Quay House, Bristol, UK Leonor Calvo, Area of Ecology, University of León, León, Spain Mirosława Ceynowa-Giełdon, Nicolaus Copernicus University, Toruń, Poland Marta Czarniecka, Wrocław University, Wrocław, Poland Adam Czarnecki, Nicolaus Copernicus University, Toruń, Poland Miłosz Deptuła, Nicolaus Copernicus University, Toruń, Poland Christiane Evers, Technical University, Braunschweig, Germany Wiesław Fałtynowicz, Wrocław University, Wrocław, Poland Anna Filbrandt-Czaja, Nicolaus Copernicus University, Toruń, Poland Marian Giertych, Uniwersity of Zielona Góra, Zielona Góra, Poland Dorota Gawenda-Kępczyńska, Collegium Medicum of Nicolaus Copernicus University, Bydgoszcz, Poland Matthias Henning, Anhalt University of Applied Sciences, Bernburg, Germany Dariusz Kamiński, Nicolaus Copernicus University, Toruń, Poland Jacek Kęsy, Nicolaus Copernicus University, Toruń, Poland Maria Kossowska, Wrocław University, Wrocław, Poland Jill Koval, Imperial College, London, UK Anna Lewandowska-Czarnecka, Nicolaus Copernicus University, Toruń, Poland Ludwik Lipnicki, Academy of Physical Education, Gorzów Wielkopolski, Poland Elena Marcos, Area of Ecology, University of León, León, Spain Adele Muscolo, University Mediterranea of Reggio Calabria, Reggio Calabria, Italy Piotr Sewerniak, Nicolaus Copernicus University, Toruń, Poland Grzegorz Swacha, Wrocław University, Wrocław, Poland Tomasz Szymura, Wrocław University, Wrocław, Poland Angela Taboada, Area of Ecology, University of León, León, Spain Jarosław Tyburski, Nicolaus Copernicus University, Toruń, Poland Liv Guri Velle, Møreforsking AS, Norway and Department of Biology, University of Bergen, Bergen, Norway